mTORC1 Overactivation as a Key Aging Factor in the Progression to Type 2 Diabetes Mellitus - Guillén, Carlos; Benito, Manuel (Frontiers in Endocrinology, 2018)
Type 2 Diabetes Mellitus (T2DM), a worldwide epidemics, is a progressive disease initially developing an insulin resistant, with a manifest pancreatic beta islets hyperplasia/hypertrophy and hyperinsulinemia. As the disease progresses, pancreatic β cells are overwhelmed and fails in their capacity to compensate insulin resistance. In addition, it is usually associated with other metabolic diseases such as hyperlipidemia, obesity and the metabolic syndrome. During the progression to T2DM there is a chronic activation of mTORC1 signaling pathway, which induces aging and acts as an endogenous inhibitor of autophagy. The complex 1 of mTOR (mTORC1) controls cell proliferation, cell growth as well as metabolism in a variety of cell types through a complex signaling network. Autophagy is involved in the recycling of cellular components for energy generation under nutrient deprivation, and serves as a complementary degradation system to the ubiquitin-proteasome pathway. Autophagy represents a protective mechanism for different cell types, including pancreatic β cells, and potentiates β cell survival across the progression to T2DM. Here, we focus our attention on the chronic overactivation of mTORC1 signaling pathway in β islets from prediabetics patients, making these cells more prone to trigger apoptosis upon several cellular stressors and allowing the progression from prediabetes to type 2 diabetes status.